Effect of Multi-Walled Carbon Nanotubes on the Water-Based Drilling Muds - Özkan, Abdullah (Muş Alparslan Üniversitesi, 2018)
This study aims to investigate of the effect of multi-walled carbon nanotubes (MWCNTs) that production by chemical vapor deposition (CVD) on the performance of water-based drilling muds (WBDM). MWCNT was added to WBDM at 0.001, 0.005, 0.01, 0.05 and 0.1 % w/v. The rheological properties of the MWCNTs added drilling fluid were determined according to the API standarts. The drilling muds at different ratios of MWCNTs addition are compared with each other, it is found that 0.1 % of MWCNTs added drilling mud has the best properties. Multi-Walled Carbon Nanotubes, Water based drilling mud, Rheological properties

Buçalışmada, kimyasal buhar biriktirme yöntemi (CVD) ile üretilen çok-duvarlıkarbon nanotüplerin (MWCNTs), su bazlı sondaj çamurlarının (WBDM) performansıüzerine  etkisinin araştırılmasıamaçlanmıştır. 0.001, 0.005, 0.01, 0.05 and 0.1 % w/v oranında MWCNTs eklenmişWBDM’lerin reolojik özellikleri API standartlarına göre tespit edilmiştir.Analiz sonuçları MWCNTs’nin iyi bir katkı maddesi olduğunu göstermiştir. Ayrıcafarklı oranlarda MWCNTs eklemesi sonucu elde edilen WBDM’ler kendi içlerindekarşılaştırıldığında, en iyi katkılama oranının % 0.1 w/v olduğu görülmüştür.
Çok Duvarlı Karbon Nanotüplerin Su Bazlı Sondaj Çamurlarına Etkisi
msufbd
Keywords: Multi-Walled Carbon Nanotubes; Water based drilling mud; Çok Duvarlı Karbon Nanotüp; Su Bazlı Sondaj Çamuru